Conditionally reprogrammed macaque endocervical cells retain steroid receptor expression and produce mucus. Issue 6 (31st March 2020) - Han, Leo; Andrews, Walker; Wong, Karsten; Jensen, Jeffrey T
Abstract: Cervical mucus produced by the endocervix plays an essential role as a hormonally induced regulator of female fertility. Cervical mucus fluctuates in both physical characteristics and in sperm penetrability in response to estrogens and progestogens. However, the mechanisms by which steroid hormones change mucus remains poorly understood. Current in vitro models have limited capability to study these questions as primary endocervical cells possess limited expansion potential, and immortalized cells lose in vivo characteristics such as steroid sensitivity. Here we overcome these limitations by establishing an in vitro primary endocervical cell culture model using conditionally reprogrammed cells (CRCs). CRC culture utilizes a Rho-kinase inhibitor and a fibroblast feeder layer to expand proliferative potential of epithelial cell types that have normally short in vitro life spans. In our studies, we produce CRC cultures using primary endocervical cells from adult female rhesus macaques ( Macaca mulatta ). We demonstrate that primary endocervical cells from the nonhuman primate can be robustly expanded using a CRC method, while retaining steroid receptor expression. Moreover, when removed from CRC conditions and switched to differentiation conditions, these cells are able to differentiate and produce mucus including MUC5B, the most prevalent mucin of the endocervix. We conclude that this method provides a promising in vitro platform for conducting mechanistic studies of cervical mucus regulation as well as for screening new therapeutic targets for fertility regulation and diseases of the endocervix. Abstract : Conditionally reprogrammed macaque endocervical cells retain steroid receptor expression and produce mucus.